Effects of antenatal betamethasone on preterm human and mouse ductus arteriosus: comparison with baboon data. (September 2018) - Shelton, Elaine; Waleh, Nahid; Plosa, Erin; Benjamin, John; Milne, Ginger; Hooper, Christopher; Ehinger, Noah; Poole, Stanley; Brown, Naoko; Seidner, Steven; McCurnin, Donald; Reese, Jeff; et al.
Abstract Background Although studies involving preterm infants ≤34 weeks gestation report a decreased incidence of patent ductus arteriosus after antenatal betamethasone, studies involving younger gestation infants report conflicting results. Methods We used preterm baboons, mice, and humans (≤276/7 weeks gestation) to examine betamethasone's effects on ductus gene expression and constriction both in vitro and in vivo. Results In mice, betamethasone increased the sensitivity of the premature ductus to the contractile effects of oxygen without altering the effects of other contractile or vasodilatory stimuli. Betamethasone's effects on oxygen sensitivity could be eliminated by inhibiting endogenous prostaglandin/nitric oxide signaling. In mice and baboons, betamethasone increased the expression of several developmentally regulated genes that mediate oxygen-induced constriction (K+ channels) and inhibit vasodilator signaling (phosphodiesterases). In human infants, betamethasone increased the rate of ductus constriction at all gestational ages. However, in infants born ≤256/7 weeks gestation, betamethasone's contractile effects were only apparent when prostaglandin signaling was inhibited, whereas at 26–27 weeks gestation, betamethasone's contractile effects were apparent even in the absence of prostaglandin inhibitors. Conclusions We speculate that betamethasone's contractile effects may be mediated through genes that are developmentally regulated. This could explain why betamethasone's effects vary according to the infant's developmental age at birth.